2000
DOI: 10.1007/s000180050505
|View full text |Cite
|
Sign up to set email alerts
|

‘Classical’ and ‘new’ diabetogens—comparison of their effects on isolated rat pancreatic islets in vitro

Abstract: This study compares functional and morphological alterations caused by application of alloxan, streptozotocin, xanthine oxidase/hypoxanthine (generation of reactive oxygen species), or S-nitroso-N-acetyl-D,L-penicillamine (SNAP, liberation of nitric oxide) to isolated rat pancreatic islets in vitro. In perifusion experiments, membrane leakage--detected by non-stimulated insulin release--was found after application of all drugs, but showed a substance-specific time pattern. Twenty-four hours after application o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0
5

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 37 publications
(29 reference statements)
3
24
0
5
Order By: Relevance
“…However, there exist some possibilities. The main effectors in STZ damage are free radicals, such as reactive oxygen species (ROS) and nitric oxide (NO) (Peschke et al 2000, González et al 2002. Androgens modulate enzymes that help cells to escape this type of damage (Ahlbom et al 1999, Aragno et al 1999.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there exist some possibilities. The main effectors in STZ damage are free radicals, such as reactive oxygen species (ROS) and nitric oxide (NO) (Peschke et al 2000, González et al 2002. Androgens modulate enzymes that help cells to escape this type of damage (Ahlbom et al 1999, Aragno et al 1999.…”
Section: Discussionmentioning
confidence: 99%
“…During STZ metabolism, various toxic intermediates are produced, including methyl cations, methyl radicals, reactive oxygen species (ROS) and nitric oxide (NO) (Peschke et al 2000, González et al 2002. Beta cells are very susceptible to oxidative changes since they possess a low antioxidative capacity (Hotta et al 1998, Kajimoto & Kaneto 2004.…”
Section: Introductionmentioning
confidence: 99%
“…In 1943, alloxan became of interest in diabetes research when Dunn and McLetchie reported that it could induce diabetes in animals [4] as a result of the specific necrosis of the pancreatic beta cells [5][6][7]. The resulting insulinopenia causes a state of experimental diabetes mellitus called 'alloxan diabetes' [4,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the STZ-DM rat differs from other common experimental models of type 1 diabetes, such as pancreatectomized animals, dexamethasone-treated type 1 diabetic rat and alloxan-induced diabetes (Ader et al, 1998;Cheta, 1998;Qi et al, 2004). An explanation to this could be the different origins of the disease and in the different modes of actions of the diabetes-inducing substances (Cheta, 1998;Peschke et al, 2000;Gai et al, 2004). To improve the usefulness of the STZ-rat model, it is of vast importance that these differences are taken into account and minimized as much as possible.…”
Section: Discussionmentioning
confidence: 99%